Anticoagulant-related nephropathy - Bunpeth, Wasin; Satirapoj, Bancha (Journal of the Nephrology Society of Thailand, 2022)
Anticoagulant-related nephropathy (ARN) is recognized form of kidney injury in which over anticoagulation with International Normalized Ratio (INR) of > 3.0 causes glomerular hemorrhage, tubular injury, and intratubular red cells and red cell casts obstruction. The main mechanism includes warfarin-induced thrombin depletion, deletion in activated protein C and endothelial protein C receptor signaling. The definite diagnosis is to kidney biopsy, which is at high risk of bleeding disorders. Early diagnosis and timely cessation of the offending medication has the potential to prevent renal progression. Treatments for ARN is crucial to balance the risks and benefits of anticoagulation and optimize treatment.